Cuidado integral durante o trabalho de parto em ambiente hospitalar na perspectiva de Jean Watson: uma revisão integrativa - Sengik, Sara Ariana Machado Boff Sberze (Universidade do Vale do Rio dos Sinos, 2021)
Introduction: Midwifery nursing has care technologies in order to favor natural childbirth, helping to prevent and correct possible dystocia in the collaborative model, as well as acting on pain during labor and delivery. It works with a focus on comprehensive care, whose scientific foundation can be found in the Theory of Human Care by Jean Watson, an American theorist and professor. Objective: To analyze the scientific production regarding care technologies in obstetric nursing care used during labor in a hospital environment from the perspective of Jean Watson. Method integrative literature review, carried out between March and April 2021 through a search in the LILACS, SCIELO and BDENF databases. Fifteen original articles were selected from 2016 to 2021. Results: The articles were organized into 3 categories: care and comprehensiveness of nursing care; limitations for care; and training as a promotion of care. Studies address nursing care through the use of nonpharmacological methods for pain relief and few advance towards comprehensive care, considering the interpersonal relationship between the nurse and the parturient. Furthermore, elements that hinder care were identified. In the training programs in obstetric nursing, the adoption of good practices based on scientific evidence was evidenced, despite some invasive interventions still present. Conclusion: The elements of human care from Watson's Theory (body, mind and spirit) are verified during nursing care during labor. Research that addresses nursing care focused on the anatomy and physiology of childbirth is recommended, considering emotional aspects and the interpersonal relationship between the nurse and the parturient.
Keywords: Enfermagem obstétrica; Trabalho de parto; Integralidade em saúde; Relações enfermeiro-paciente; Obstetric nursing; Labor; Health comprehensiveness; Nurse-patient relationships